On security in wireless local area network - Tran Ngọc Bảo; Nguyen Đình Thúc; Tran , Đan Thư (Journal of Technical Education Science, 2011)
Confidentiality is one of the important security services for wireless local area network (WLAN), to ensure the information is confidential and integrity. This problem mainly focus on commercial solutions that apply popular encryption algorithms such as: RC4 in WEP (Wired Equivalent Privacy), WPA (Wi-Fi Protected Access); AES (Advanced Encryption Standard) in WPA2. Virtual private network (VPN) solution also uses in products of Wi-Fi vendor. According to VPN solution approach, we focused on the scalability of block cipher systems such as Hill cipher, matrix cipher and AES. In these crypto systems, S-box is significant non-linear component. In this paper, we propose a new approach to represent general S-Box based on a given non-linear function to increases the complexity of algebraic expression and size of S-Box. In experiment with size of 8, proposed S-Box can archive the maximum number of terms (255 terms) and therefore it can be used to replace the classical S-Box component in the original AES. Furthermore, proposed S-Box inherits all good cryptographic characteristics of the original AES S-Box, such as nonlinearity, differential uniformity, and strict avalanche